2017
DOI: 10.1515/abm-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and etiology of maxillofacial trauma: a retrospective analysis of King Chulalongkorn Memorial Hospital in the past decade

Abstract: Background: Maxillofacial injury is a common injury in trauma patients. The incidence, associated injuries and causes have been never reported for King Chulalongkorn Memorial Hospital (KCMH). Objectives: To report the incidence, associated injuries, age groups, treatments, and behavioral risks in maxillofacial patients who were admitted to KCMH in the past decade. Methods: We conducted a retrospective descriptive analysis of patients from January 1, 2006, to December 31, 2015, to evaluate the age groups, cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…In this study, almost half of MCA victims were below the age of 21 years (46.0%). This is in agreement with recent findings of a 10-year study regarding the incidence and etiology of MFF done by Pungrasmi and Haetanurak in Thailand which report MCA as the most common cause of MFF and half of patients were 11-30 years old [35]. This is possibly because the young motorcyclists are inexperienced, lack the proper riding skills, often ride carelessly or recklessly, and tend to violate traffic laws, for example, by not using helmets, running red lights, and exceeding the speed limit [20, 36, 37].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, almost half of MCA victims were below the age of 21 years (46.0%). This is in agreement with recent findings of a 10-year study regarding the incidence and etiology of MFF done by Pungrasmi and Haetanurak in Thailand which report MCA as the most common cause of MFF and half of patients were 11-30 years old [35]. This is possibly because the young motorcyclists are inexperienced, lack the proper riding skills, often ride carelessly or recklessly, and tend to violate traffic laws, for example, by not using helmets, running red lights, and exceeding the speed limit [20, 36, 37].…”
Section: Discussionsupporting
confidence: 92%
“…The age-wise distribution shows that the third decade has the highest number of facial injuries followed by the fourth, showing accordance with other studies. 4 , 11 , 12 The bony fractures have lower mean age (29.54 years) than the soft tissue injury (32.20 years) which is also similar to study by Prasad et al 13 This young predominance of facial injuries maybe because of young male are involved in activities like sports, interpersonal violence, high speed traveling and drinking and driving. 14 As development occurs etiology for facial injuries also changes.…”
Section: Discussionsupporting
confidence: 77%
“…20 In this study, we observed the highest percentage of fracture occurred in the mid-face, followed by a lower third of the face. The higher prevalence of the midface fracture is also reported in studies 5,11 in contrast to other studies where more incidence of fracture in lower facial third is reported. 2,4,13,16 This higher prevalence of the midfacial injury may be attributed to the wider face and prominent malar bone of Asian people.…”
Section: Discussionmentioning
confidence: 43%
“…It has been reported that 20%–60% of all people injured in RTAs tend to have some form of maxillofacial injury. [12131415] The chances of these injuries increase even more when helmets are not used routinely; these injuries are not only traumatic but also cause significant problems physiologically, functionally, and esthetically. The head-and-the neck region is the most exposed part of the body, making it a point of direct injury in RTAs.…”
Section: Introductionmentioning
confidence: 99%